The Southern Patriot, vol.30, no.10, December 1972 - (:unkn) unknown (Louisville, KY: Southern Conference Educational Fund (SCEF), 1972)
The Southern Patriot, vol.30, no.10, December 1972. Louisville, KY: Southern Conference Educational Fund (SCEF). The Southern Patriot, Valdosta State University Archives and Special Collections.
1 Electronic record(s), 8 image scans.
Keywords: Newspapers; Periodicals; Civil rights